A Study of Bidirectional Electric Vehicle Charging using MATLAB Simulink - Anuja, G.; Rhenie, S. E. Kepha; Khiangte, Remsangpuii; Sridhar, M. R.; Sridharan, R.; Elango, S. (Journal of Electronics and Informatics, 2024)
On considering Electric Vehicles, the rise of Vehicle-to-Grid(V2G) concept has been accompanied with lots of advantages. The V2G technology ensures that no extra electricity needs to be consumed from the grid. It helps the power grid on a larger scale. It enables a bidirectional power flow between the EV battery and the grid. Bidirectional Buck- Boost Converter helps in grid stabilization, financial gains, and effective energy management. The DC-DC Converter does two functions: matching the battery voltage to the motor's rated voltage and controlling power flow under steady-state and transient conditions. The Proportional-Integral (PI) controller is used to correct the errors between commanded set point and the actual value based on feedback. The efficiency of the converter can be increased by using PI controller.
Keywords: Bidirectional DC-DC converter; G2V; V2G; electric vehicle applications